Discricionariedade e mandato de bancos centrais em contexto de desregulamentação financeira: o caso do Federal Reserve na crise de 2007 a 2009 - Mattos, Olívia Maria Bullio (2010)
In mid-2007, the world faced one of the biggest crisis capitalism ever experienced, called the subprime crisis, which originated in the US housing market. The Federal Reserve (Fed) had to act promptly, trying to rescue the markets. However, the Federal Reserve, which had always been pragmatic, found itself in great distress when the traditional tools of monetary policy were not enough to stop the liquidity crisis. The Fed had to act aggressively both as a lender of last resort and expanding the monetary base to halt the risk of a widespread "default" in the inter-bank market. Using changes in the size and composition of the Fed's Balance Sheet From July of 2007 to September of 2009, this dissertation analyses the actions taken and new tools created to fight the crisis. Initially, the dissertation presents the prevailing thesis up to the subprime crisis, which were the financial deregulation and the monetary authority's goal of price stability. The dissertation then discusses the Post- Keynesians and Minsky's take of the capitalistic economy, a more adequate view to understand the crisis and the preceding financial processes. In conclusion, the lessons learned from the subprime crisis are that we should rethink how we regulate financial institutions and products created by such institutions in pursue of profit; we should also rethink the way we do monetary policy and its objectives